Challenge on Picturing Indonesian Disaster Through Drone Journalism - Widiatmojo, Radityo; Nasvian, Moch Fuad; Natalia, Wahyu Kristian; Wibowo, Bhekti Setyo; Tri Atmaji, Lutfi; Lakshmi Devi, Patricia Raniza (Jogjakarta Communication Conference (JCC), 2023)
Every year, various natural disasters strike Indonesia, and journalism activities play an important role in disaster communication. This study aims to find out how the challenges of picturing natural disasters in Indonesia through drone journalism are. For this reason, the researcher chose key informants who have international reputations, namely Willy Kurniawan from Reuters and Budi Candra who represent the National News Agency, Antara. By using thematic analysis, the results of in-depth interviews will be selected and grouped and visualized using the miro application. The results of the study show that drone journalism is a form of disaster communication that presents aerial photographs which function to show the impact and escalation of disasters. The challenges of drone journalism include ethical factors, copyrights, and technology for sending images during a disaster. In the aspect of disaster management and disaster communication, drone journalism plays a role as a supplement aerial information for evacuation and mitigation in the "during disaster" and "after disaster" phase. The next challenge is in the non-disaster phase, where the collaboration of multiple stakeholders is needed to make drone journalism can become a tool for educating people in disaster-prone areas.